Pemanfaatan Platform Merdeka Mengajar (PMM) Untuk Meningkatkan Kinerja Guru di MI No 06/E72 Tanjung Rawang - Khoyyir Ridho; Imran, Imran (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to explore in depth the utilization of the Merdeka Mengajar Platform (PMM) in improving teacher performance at MI No. 06/E72 Tanjung Rawang. Employing a qualitative approach with a case study method, data were collected through observation, semi-structured interviews with teachers and school administrators, and documentation review. The findings reveal that PMM plays a crucial role in enhancing teachers’ professional competence by providing easy access to structured learning modules, inspirational videos, and updated teaching resources. It also supports collaboration and sharing of best practices through online learning communities, enabling teachers to discuss challenges, exchange teaching strategies, and receive feedback. Furthermore, PMM contributes to improved classroom management and assessment practices by offering digital tools that support lesson planning and formative evaluation. The platform also fosters reflection and continuous self-improvement through regular evaluations, self-assessments, and personalized recommendations. Despite these benefits, challenges persist, including unstable internet access, limited technological devices, and difficulties adapting instruction to the Merdeka Curriculum. This study recommends improving technological infrastructure, organizing regular training, and strengthening teacher learning communities to maximize the benefits of PMM. These findings underscore the strategic role of PMM as an innovative tool for teacher professional development and student learning improvement.